2020
DOI: 10.11604/pamj.2020.36.99.21873
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of groove pancreatitis: a case report

Abstract: Groove pancreatitis (GP) is a rare form of chronic pancreatitis involving the groove area bound by the pancreatic head, the duodenum, and the common bile duct. The diagnosis of this entity is challenging since it can mimic pancreatic carcinoma. We herein report the case of groove pancreatitis diagnosed in a 37 year old men, with a past history of chronic alcohol consumption. The patient was admitted for several times over the past three years because of recurrent alcohol-induced pancreatitis. The diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Surgical treatment options may include pancreaticoduodenectomy and gastrojejunostomy, as well as choledochotomy with T-tube drainage (11,28,29). Pancreaticoduodenectomy has been shown to markedly reduce the use of painkillers and completely eliminate clinical symptoms in patients with late-stage complications such as obstruction and severe pain, but there is a lack of relevant outcome studies available to confirm its efficacy (6,12,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment options may include pancreaticoduodenectomy and gastrojejunostomy, as well as choledochotomy with T-tube drainage (11,28,29). Pancreaticoduodenectomy has been shown to markedly reduce the use of painkillers and completely eliminate clinical symptoms in patients with late-stage complications such as obstruction and severe pain, but there is a lack of relevant outcome studies available to confirm its efficacy (6,12,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the pressure within the Santorini duct increases, ultimately forming pseudocysts [8]. Brunner gland hyperplasia, ectopic pancreatic tissue, true duodenal wall cysts, history of gastrectomy, gastroduodenal ulcer, biliary diseases, and the presence of anatomic abnormalities are also associated with the disease [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In case patients are not clinically improved, present with complications, or the possibility of malignancy cannot be ruled out, the most suitable approach is surgery. Pancreatoduodenectomy, with Whipple's procedure or with preservation of pylorus-Longmire technique, is the most commonly used method because it provides both a definitive cure of the symptoms and resection of possible malignancy [4,7,10]. Casetti et al observed a percentage of 76% pain remission in patients after pancreatoduodenectomy [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a hyperplasia of the Brunner's glands, which is the most common finding in histological analysis [5] and causes occlusion or dysfunction of the minor papilla [6][7][8]. Other causes of minor papilla dysfunction that are related to this entity are a history of gastrectomy, gastroduodenal ulcer, and biliary diseases and the presence of anatomic abnormalities such as ectopic pancreatic tissue in the duodenum or pancreatic divisum [10,11]. The initial clinical presentation is nonspecific, and the most common manifestations are upper abdominal pain, nausea, vomiting, and weight loss, primarily due to duodenal obstruction [5,8,12].…”
Section: Discussionmentioning
confidence: 99%